2022
DOI: 10.1007/s00401-022-02438-z
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle provides the immunological micro-milieu for specific plasma cells in anti-synthetase syndrome-associated myositis

Abstract: Anti-synthetase syndrome (ASyS)-associated myositis is a major subgroup of the idiopathic inflammatory myopathies (IIM) and is characterized by disease chronicity with musculoskeletal, dermatological and pulmonary manifestations. One of eight autoantibodies against the aminoacyl-transferase RNA synthetases (ARS) is detectable in the serum of affected patients. However, disease-specific therapeutic approaches have not yet been established.To obtain a deeper understanding of the underlying pathogenesis and to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 80 publications
2
20
0
1
Order By: Relevance
“…ARS, antisynthetase syndrome (all subtypes); DM, dermatomyositis; IBM, inclusion body myositis; IMNM, immune-mediated necrotizing myopathy; P-MM, possible myositis mimics. pathological features among these ASS subtypes including PFN, MHC class I upregulation and prominent perifascicular MHC class II expression; only one PL-12 ASS had negative MHC class II expression [41]. In line with the pathological features, the proteomic profiling of muscle associated with these three antibodies show no significant difference [ 41].…”
Section: Discussionmentioning
confidence: 82%
“…ARS, antisynthetase syndrome (all subtypes); DM, dermatomyositis; IBM, inclusion body myositis; IMNM, immune-mediated necrotizing myopathy; P-MM, possible myositis mimics. pathological features among these ASS subtypes including PFN, MHC class I upregulation and prominent perifascicular MHC class II expression; only one PL-12 ASS had negative MHC class II expression [41]. In line with the pathological features, the proteomic profiling of muscle associated with these three antibodies show no significant difference [ 41].…”
Section: Discussionmentioning
confidence: 82%
“…Two previous studies reported elevated levels of circulating Tfh cells in IIM (PM and DM patients) compared to healthy controls [ 25 , 26 ]. Further, we previously substantiated the presence of Tfh cells in ASyS muscle in comparison to non-diseased controls [ 21 ]. Promoting antigen-specific B cells [ 27 ], Tfh cells might provide a pro-stimulatory framework for B cell pathology in ASyS.…”
Section: Discussionmentioning
confidence: 95%
“…First, ASyS is characterized by antibodies against the aminoacyl-transferase RNA synthetases, commonly against Jo-1, OJ, PL-7 or PL-12. To better understand disease specific pathways of autoimmunity, we investigated ASyS pathology in a previous study [ 21 ]. Here, we identified an extra-medullary inflammatory micro-milieu maintaining activated B cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent immunophenotyping work in a large cohort of JDM patients that found simultaneous expansion of CXCR5-central memory B cells and Th2 cells provides support for further investigation into extra-follicular B-T cell help in JDM (15). Alternatively, this skewing could represent more mature B cells homing to tissues as has been described in antisynthetase syndrome (48,49). Functional work to support or negate the extrafollicular pathway in JDM will be critical to determine if this is a targetable pathway therapeutically.…”
Section: Discussionmentioning
confidence: 84%